PENGARUH SUHU DAN LAMA THAWING DI DATARAN RENDAH TERHADAP KUALITAS SEMEN BEKU SAPI BRAHMAN - Muhammad Fauzan; Madi Hartono; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Thawing is a method by melting back of semen that had been frozen prior to artificialinsemination (AI). The temperature and duration of thawing has a major influence on the state of thespermatozoa, especially the integrity of spermatozoa in the semen. The combination of temperatureand duration of thawing that will either be able to prevent damage to sperm , so it still has a highfertility rate. In common, lowland is an area that has low temperature and humidity, so it will have aneffect of thawing’s temperature. The purpose of this study was to determine the temperature andduration of thawing of Brahman’s frozen semen which have the most optimal to get used inartificial inseminations in lowlands area.Research was conducted in March 2014 using a completely randomized design (CRD) with a3x3 factorial. The first factor is the temperature (34°C, 37°C, and 40°C) and Factor II is duration ofthawing (10 seconds, 15 seconds, and 20 seconds) with 3 replications. Parameters observed in thisstudy is the percentage of sperm motility and live spermatozoa. The results were analyzed usingANOVA and Duncan's test at the advanced level of 5 % and 1%. The results showed that temperatureand duration of thawing give effects to the quality of the frozen semen of Brahman cattle, but has nointeraction between them. The most good quality spermatozoa at a temperature of 40ºC spermmotility is 37,77% and the percentage of live spermatozoa is a 40,83%. Duration of thawing at 15seconds sperm motility is 38,33% and the percentage of live spermatozoa is a 39,77%.